Meta-analysis of the interaction between serotonin transporter promoter variant, stress, and posttraumatic stress disorder. Issue 1 (December 2017) - Zhao, Mingzhe; Yang, Jiarun; Wang, Wenbo; Ma, Jingsong; Zhang, Jian; Zhao, Xueyan; Qiu, Xiaohui; Yang, Xiuxian; Qiao, Zhengxue; Song, Xuejia; Wang, Lin; Jiang, Shixiang; et al.
Abstract Exposure to stress predicts the occurrence of posttraumatic stress disorder (PTSD) in individuals harboring the serotonin transporter promoter variant5-HTTLPR . We carried out a meta-analysis of studies investigating the interaction between5-HTTLPR, stress, and PTSD to clarify the interrelatedness of these factors. We reviewed all relevant studies published in English before May 2016. The Lipták–Stouffer z-score method for meta-analysis was applied to combined data. The z score was separately calculated for the stressful life events, childhood adversity, bi- and triallelic loci, and cross-sectional and longitudinal studies subgroups. A total of 14 studies with 15, 883 subjects met our inclusion criteria. We found strong evidence that the presence of5-HTTLPR influenced the relationship between stress and PTSD (P = 0.00003), with the strongest effects observed in the cross-sectional and longitudinal groups (P = 0.01 and 2.0 × 10−6, respectively). Stressful life events and childhood adversity separately interacted with5-HTTLPR in PTSD (P = 2.0 × 10−8 and 0.003, respectively). When the studies were stratified by locus classification, the evidence was stronger for the triallelic (P = 4.0 × 10−8 ) than for the biallelic (P = 0.054) locus subgroup. There was strong evidence that5-HTTLPR influences the relationship between stress and PTSD.